ANALYSE DE LA TRESORERIE DE LA MAIRIE DE KINDU DE 2009 A 2013 - MUPASA, MUPASA BIN (IJRDO - Journal of Business Management, 2022)
Interesting us in the treasury of the town hall of Kindu, capital of the Province of Ma,iema, our results reveal that during the five years selected for this research, the net treasury was not constant. At the end of the period (2013) cash was negative, while at the beginning its sign was positive ; this situation proves an excessive disbursement copared to the collection. Our results show that the closing balance in 2013 was positive, evaluated at 3.375.475 FC thanks to the accumulation of cash from previous periods. This amount represents the cash or amount available on sight, easily mobilized at the Kindu. The general trend in the evolution of net cash for the five years period used in the context of this research is downward, despite the exponential increase observed between 2010 and 2011.